The Impact of Industry Concentration on Stability: The Case of Indonesian Islamic-Commercial Banks - Santoso, Teguh; Firmansyah, Egi Arvian; Sapulette, Militcyano Samuel; Setiawan, Maman (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims at investigating the impact of the banking industry’s concentration on the stability of Islamic commercial banks in Indonesia. This study used a single country setting of 14 Islamic-commercial banks in Indonesia from 2011 to 2020. The data utilized in this study comprised all Islamic-commercial banks' assets in Indonesia, excluding commercial banks with Islamic business units. The influence of concentration level on the stability of Islamic-commercial banks was investigated using a panel data model. According to Hausman's test, the fixed-effect model is more suitable than the random-effect model. The findings indicate that the “concentration-stability” hypothesis was supported-robust using two concentration level measurements: CR4 and HHI. It is implied that banks tended to be more stable at the higher competition level. From the bank’s specific characteristics, only the cost-to-income ratio significantly influenced the bank's stability, as expected. Other bank-specific characteristics, such as bank size, credit risk, and income diversity, had no substantial influence on observed bank stability. A robustness check was performed by estimating new models that included multiple control variables that did not change the effect of concentration level on the bank’s stability. This study adds to the literature by demonstrating the “concentration-stability” hypothesis in the Indonesian Islamic-commercial banking industry. Moreover, this study’s results confirm the previous study’s findings using different methods and measures of industry concentration. In addition, this study is relevant in the context of the merger action of three large Islamic commercial banks.